Protist–Lactic Acid Bacteria Co-Culture as a Strategy to Bioaccumulate Polyunsaturated Fatty Acids in the Protist Aurantiochytrium sp. T66 - Luis Marileo; Jacqueline Acuña; Joaquin Rilling; Paola Díaz; Antonio Luca Langellotti; Giovanni Luca Russo; Patricio Javier Barra; Patricio Dantagnan; Sharon Viscardi (Marine Drugs, 2023)
Thraustochytrids are aquatic unicellular protists organisms that represent an important reservoir of a wide range of bioactive compounds, such as essential polyunsaturated fatty acids (PUFAs) such as arachidonic acid (ARA), docosahexaenoic acid (DHA), eicosapentaenoic acid (EPA), which are involved in the regulation of the immune system. In this study, we explore the use of co-cultures of Aurantiochytrium sp. and bacteria as a biotechnological tool capable of stimulating PUFA bioaccumulation. In particular, the co-culture of lactic acid bacteria and the protist Aurantiochytrium sp. T66 induce PUFA bioaccumulation, and the lipid profile was evaluated in cultures at different inoculation times, with two different strains of lactic acid bacteria capable of producing the tryptophan dependent auxins, and one strain of Azospirillum sp., as a reference for auxin production. Our results showed that the Lentilactobacillus kefiri K6.10 strain inoculated at 72 h gives the best PUFA content (30.89 mg g−1 biomass) measured at 144 h of culture, three times higher than the control (8.87 mg g−1 biomass). Co-culture can lead to the generation of complex biomasses with higher added value for developing aquafeed supplements.